SISTEM INFORMASI PERKEMBANGAN PENDIDIKAN PADA ANAK USIA DINI (AUD) BERBASIS WEB PADA TAMAN KANAK-KANAK (TK) YAYASAN AL MUALLAFAH - Pangestu Smita Gusti (2020)
The use of computer technology as a supporting tool in information systems can provide better and more accurate information for users, one of which is an information system for early childhood education development. Therefore, we need an information system to help the process of managing data to produce useful information. The use of the web as an information system has not been applied to the Al Muallafah. The data processing process of early childhood education development is still conventional so that the data has not been centered on one database. In addition, the possibility of human error and data duplication is very high. With the web-based information system for early childhood education development can help facilitate the recording, processing, storage, reporting, and presentation of academic data and information. The design of this web-based information system was built using the PIECES analysis method and prototyping development method using the PHP programming language and black box testing to do the system testing. The results of this research are information systems for early childhood education development that can be used by the Al Muallafah's for Kindergarten which are expected to handle the process of recording, processing, storing, reporting, and presenting academic data and information in the form of web-based information systems.